PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Rafika Melani; Idrianita Anis (Jurnal Akuntansi Trisakti, 2017)
The purpose of this study was to examine the influence of corporate social responsibility disclosure, the effectiveness of the board of commissioners, institutional ownership and implementation of SFAS 60 (revised 2010) on the enterprise risk management disclosure. The data used in this research is secondary data, , obtained the annual report of the banking industry company listed on the Indonesia Stock Exchange. The population of this research is the banking industry companies listed in Indonesia Stock Exchange during the years 2009-2015, amounting to 161 companies. The collection of samples using purposive sampling method by selecting predefined criteria. This study uses multiple regression analysis. The results of this study indicate that not all independent variables showed a significant effect on the dependent variable. CSR disclosure and effectiveness of the board of commissioners has a positive effect on enterprise risk management disclosure. Meanwhile, institutional ownership has no effect on the enterprise risk management disclosure and the application of SFAS 60 (Revised 2010) has no effect on the enterprise risk management disclosure